Pegylated granulocyte colony stimulating factor versus non-pegylated granulocyte colony stimulating factor for peripheral stem cell mobilization - Kuan, Jewwin; Su, Anselmting; Leong, Chooifun; Tharyan, Prathap (John Wiley and Sons Ltd, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To compare the efficacy and safety of pegylated G-CSF with non-pegylated G-CSF for peripheral blood stem cell mobilization. © 2016 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd